Increased vulnerability of Arctic potential ice roads under climate change - Yuanbiao Dong; Pengfeng Xiao; Xueliang Zhang; Daqing Ge; Junchuan Yu; Yangyang Chen; Qiong Wu; Yanni Ma; Rongyuan Liu; Wenbo Luan; Hao Liu; Jie Bai (Communications Earth & Environment)
Abstract Temporary ice roads built by the process of snow compaction, watering, and icing during cold winters are lifelines for land access in remote Arctic. In the context of the Arctic amplified warming, the vulnerability of potential ice roads under the influence of complex climate system remains unclear. Here, we construct a potential ice road assessment model that allows quantization of the climatic suitability of potential ice roads in the Arctic. Using satellite remote sensing and meteorological data, we find changes in surface air temperature and snow cover reduced the climatic suitability of potential ice roads during 1979–2017. Spatially, potential ice roads in North America face more immediate threats due to decreased snow depth compared to Eurasia. Before the end of the 21st century, we project a further decline in the climatic suitability of potential ice roads, primarily due to increasing surface air temperatures and decreasing permafrost stability. Taking precious metal/diamond exploration as an example, we conclude that mining activities associated with ice roads will face access difficulties by 2050–2100 due to the decreased potential ice roads. These results give new insights into the challenges and opportunities of Arctic overland travel.